Social change and high school opportunity in Guyana and Jamaica: 1957-1967 - Bynoe, Jacob Galton (1972)
This study examined efforts made to lessen inequalities in educational opportunities in Guyana and Jamaica during the 1950s and 1960s, and assessed the results achieved. Specifically, it enquired into the results of measures instituted during 1957 to 1967 to reduce inequalities in representation of different groups among high school free-place winners. It is hypothesized that despite legislative and organizational changes, formerly deprived groups still remained at a considerable disadvantage in their chances for high school selection. For both countries, groups were classified on the basis of four differentiating characteristics: parental occupation, regional background, sex, and type of previous school attended. For Guyana, ethnic background was included. Analysis of Ministry of Education records of all free place winners in 1967 revealed that the position of the traditionally less privileged rural, and skilled, semi-skilled, and unskilled groups remained far below public expectations and official claims. However, the disadvantage suffered in Guyana by East Indians as a group was rapidly and almost completely eliminated with increased participation of this group in the governmental machinery. Some of the social and economic factors that appeared to contribute to the frustration of efforts for the general expansion and equalization of high school opportunity in both countries were identified as the scarcity of economic resources, the system of rewards, the kinds of employment opportunities available, and commitment on the part of various sections of the community to traditional elitist educational values
Keywords: Equal education